Integrated profiling of metaplastic breast cancer identifies putative master regulators of intratumoral heterogeneity - Yufan Feng; Albert Xiong; Onkar Mulay; Anna Sokolova; Malcolm Lim; Benjamin Van Haeringen; Natasha McGuire; Xavier de Luca; Peter T. Simpson; Quan Nguyen; Sunil R. Lakhani; Amy E. McCart Reed (npj Breast Cancer)
Abstract Metaplastic breast cancer (MpBC) is defined by the presence of various morphological elements, typically biphasic, with epithelial (e.g. no-special type (NST), squamous) and mesenchymal (e.g. spindle, chondroid, osteoid) components. The established clonality of the different components favours an evolution model encompassing either a multipotent progenitor, or a linear metaplastic conversion. We used methylation profiling and showed that different morphologies have specific methylation profiles. Furthermore, our spatial transcriptomic approach, using 10× Genomics Visium and trajectory analysis, evidenced that spindle cells form a transition between the originating carcinoma of no-special type (NST) and pleomorphic regions, with osteoid differentiation likely to be an end-stage fate of the chondroid growth pattern, supporting the conversion model of lineage differentiation. We have also identified a series of master transcription factors likely to regulate these processes, and are significantly associated with metaplastic-like clinical features. This data further supports the conversion model of metaplasia and warrants functional analysis.